Visible-light Degradation of Methylene Blue using Energy-Efficient Carbon-Doped TiO2: Kinetic Study and Mechanism - Lau, Alysa; Goh, Chien Yong; Guo, Yubei; Alsultan, Abdulkareem Ghassan; Yun Hin, Taufiq-Yap; Nurhadi, Mukhamad; Lai, Sin Yuan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Wastewater pollution is mainly produced from the dye textile industry and the most widely used photocatalyst to degrade dye textile is TiO2 due to its photostability, low toxicity, and low production cost. However, TiO2 is only responsive under UV light; thus, our study is to extend the TiO2 absorption light to visible region via doping of bio-based carbon source, viz. ascorbic acid, to produce carbon-doped TiO2. The carbon-doped TiO2 were solvothermally synthesized with varying carbon loadings (10, 30, and 50 wt%) and calcination temperatures (250, 300, and 400 oC). The functional groups of carbon-doped TiO2 were determined, which the carbonyl groups (C=O) at 1700 cm-1, alkenyl groups (C=C) at 1630-1670 cm-1, hydroxyl groups at 3380-3390 cm-1, and TiO2 appeared at 450 cm-1. The absorption spectra shifted from UV to visible-light region and the band gap was reduced compared to undoped TiO2. The photoluminescence results showed that the surface oxygen vacancies (SOVs) are generated for carbon-doped TiO2. The Ti–C bond formation was proved through diffractogram peak shifting, while the crystallite sizes decrease with increasing carbon amount and decreasing calcination temperature. The highest methylene blue photodegradation of 89.53% was achieved by 30 wt%C-TiO2-250 photocatalyst at pH 10 under 2 h visible light irradiation. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).